Pengembangan Snakes And Ladder Sinergi Meningkatkan Self Esteem Dan Literasi Sains Siswa Kelas 4 SDN Ngadipuro 04 - Ni'mah, Naili; Fatih, Muhamad; Alfi, Cindya (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study aims to develop a Snakes and Ladder Synergy media to improve the self-esteem and science literacy skills of fourth-grade students at SDN Ngadipuro 04 Elementary School in Blitar Regency. This study applies a research and development (R&D) method by adopting a simplified version of Borg and Gall's stages, supported by a one-group pretest-posttest design. Data was collected through observation, interviews, questionnaires, and tests, with instruments validated for validity and reliability. A total of 16 fourth-grade students at SDN Ngadipuro 04 served as research subjects. The product validation results showed an average percentage of 92% for subject matter experts and 96% for media experts, with an overall average of 94%, indicating that the Snakes and Ladder Synergy media is “highly valid” and suitable for use in learning. The effectiveness of the product was tested using a paired sample t-test, showing a significance value of 0.57 (>0.05) for self-esteem, meaning there was no statistically significant increase in self-esteem. Conversely, the significance value of 0.00 (<0.05) for science literacy indicates an improvement in students' science literacy skills. The multivariate MANOVA test showed a significant simultaneous effect on the improvement of self-esteem and science literacy (sig. 0.00 <0.05). However, partial analysis showed a more dominant effect on science literacy, while self-esteem did not show a significant effect in the partial analysis. This media was proven effective in improving science literacy, although the impact on self-esteem requires further study.